2010
DOI: 10.1016/j.otohns.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life and health utility burden of recurrent respiratory papillomatosis in children

Abstract: This is the first study to use validated measures of health utility, voice-related quality of life, and psychosocial impact. This information has public health implications, providing essential parameters for accurate modeling studies and cost-utility analysis of future interventions, including different human papilloma virus vaccination strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…The finding of impaired quality of life in young Mexican patients with recurrent respiratory papillomatosis is consistent with reports by Lindman et al 6 in North American patients and Chadha et al 7 in Canadian patients. The current study also showed that physical performance and interaction with peers may be poorer in children with recurrent papillomatosis than in those with chronic otitis media.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding of impaired quality of life in young Mexican patients with recurrent respiratory papillomatosis is consistent with reports by Lindman et al 6 in North American patients and Chadha et al 7 in Canadian patients. The current study also showed that physical performance and interaction with peers may be poorer in children with recurrent papillomatosis than in those with chronic otitis media.…”
Section: Discussionsupporting
confidence: 91%
“…3 Young age at diagnosis is significantly associated with disease progression in children with lesions restricted to the larynx at the time of diagnosis, and patients who require tracheostomy are more likely to manifest progressive disease extending to new sites. 7 The World Health Organization defines health as the state of complete physical, mental and social wellbeing, and not merely the absence of disease or infirmity. 5 However, studies on the impact of the disease on the quality of life of children and teenagers are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This study supports the significant morbidity associated with the diagnosis of RRP in a child. The chronic relapsing nature of RRP, and associated significant morbidity and effects upon quality of life, as well as the lack of curative surgical or medical treatments, support the role of primary prevention of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have reported utility values associated with dysphonia for the purpose of cost utility analysis (CUA), which requires valuation for health states as well as cost information. 1,17 Within otolaryngology these studies have focused on head and neck cancer, [18][19][20][21][22][23][24] juvenile onset respiratory papillomatosis, 25 and recurrent nerve injury following thyroid surgery. [26][27][28] However, quality and description of utility elicitation techniques are deficient; most do not include methodological descriptions or confidence intervals around estimates, limiting their applicability.…”
Section: Discussionmentioning
confidence: 99%